Kompetensi Pedagogik Guru Sekolah Inklusi di Indonesia (Suatu Pendekatan Systematic Review) - Ratna Sari Wulandari; Wiwin Hendriani (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aimed to investigate the pedagogical competences of inclusive school teachers, especially in Indonesia. The research method used was a systematic review. The electronic data bases used were Wiley, ScienceDirect, and Google Scholar. The initial search found 24 journals and were then selected based on exclusive criteria, in which there were seven journals identified using thematic data analysis techniques. The result of this study showed that the pedagogical competence of teachers in inclusive schools, especially in Indonesia, is relatively low. Several factors which inhibit teacher pedagogic competence, which are different teachers’ educational backgrounds, teachers do not understand students’ characteristics which cause difficulty to identify different student needs, and teachers have difficulty to evaluate student learning processes.